Manajemen Pembelajaran Guru PAI Dalam Meningkatkan Hasil Belajar Peserta Didik Sekolah Dasar Yayasan Trio Batanghari - Atika Dhanasari; Siti Sakinah; Try Susanti (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to analyze the learning management of Islamic Education (PAI) teachers in improving student learning outcomes at Yayasan Trio Batanghari Elementary School. The research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. The results show that learning management by PAI teachers includes thorough planning, the implementation of active learning methods, and continuous evaluation. PAI teachers play an important role in creating a conducive learning environment and motivating students. The main obstacle is the limited learning facilities, but this can be overcome through teacher creativity. Effective learning management has a positive impact on improving students' learning outcomes and characterKeywords: Learning Management, Islamic Education Teacher, Learning Outcomes, Elementary School